2021
DOI: 10.1111/eje.12673
|View full text |Cite
|
Sign up to set email alerts
|

The motivation and confidence in choosing dentistry as a career amongst dental students: A mixed‐methods study

Abstract: Objectives An insight into students’ motivation and confidence in the choice of entering and remaining in dental education is essential. The understanding of how choices are made can help universities in the planning of admission policies. This study aimed to evaluate the career choice influences, motivation and confidence in the choices made into dental education. Methods A mixed‐method design was employed, using both quantitative and qualitative data. One hundred seventy‐three questionnaires were distributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
1
4
0
1
Order By: Relevance
“…A study of the motivation and confidence of dental students showed that students were disappointed with the program’s content and its integration with the medical curriculum. Many students reported that they had not noticed the breakdown of the didactic program along with the introduction to the dental subjects, that they had changed their minds about their choices and that some were even unhappy with their choices [ 36 ]. The element of confidence is essential in career choice and acts as a motivator, enabling students to accept their chosen career with greater satisfaction during difficult times that await them during their academic years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of the motivation and confidence of dental students showed that students were disappointed with the program’s content and its integration with the medical curriculum. Many students reported that they had not noticed the breakdown of the didactic program along with the introduction to the dental subjects, that they had changed their minds about their choices and that some were even unhappy with their choices [ 36 ]. The element of confidence is essential in career choice and acts as a motivator, enabling students to accept their chosen career with greater satisfaction during difficult times that await them during their academic years.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study revealed that dental students had more doubts about their choice of specialty during the preclinical years. This doubt decreased as students entered their clinical years [ 36 ]. However, a study by Çapan et al [ 24 ] reported that 30.1% of fourth- and fifth-year dental students wanted to change their careers.…”
Section: Discussionmentioning
confidence: 99%
“…Faktor ini dipengaruhi oleh budaya dan norma mengenai peran wanita dalam keluarga yang mana wanita merupakan responden terbanyak dalam penelitian ini. 21 Preferensi terhadap kedokteran gigi pada siswa sekolah menengah cukup tinggi, namun preferensi mahasiswa terhadap kedokteran gigi lebih rendah. Hal ini disebabkan oleh kurangnya konseling…”
Section: Andalas Dental Journalunclassified
“…2 Previously, the career path used to be predetermined, whereas now there is a career planning process. 3 The factors that contribute to this decision may broadly be grouped under intrinsic, extrinsic, vacations, finances, and prestige. 4 The rapidly increasing numbers of medical colleges in Pakistan, asks for faculty training for having core knowledge, and competency to apply teaching methodologies based on adult learning principles.…”
Section: Introductionmentioning
confidence: 99%